Dynamic analysis of the primary breakup of an annular energetic liquid jet injecting into a confined space - Sun, Ming-liang; Liu, Ning; Zhang, Xiang-yan (Journal of physics. Conference series, 2020)
The Large Eddy Simulation (LES) with the Volume of Fluid (VOF) method was carried out to investigate the primary breakup dynamic mechanism of an annular energetic liquid jet injecting into a confined space. The gas vortex structure and the liquid jet formation were visualized by tracking the evolution of the phase velocity and the interface location, and hence the coalescence process of the goblet-shaped liquid jet from the annular liquid jet was reproduced. Simulation results indicate that the first coalescence is caused by the Rayleigh-Taylor instability, which is generated by the interaction between the liquid jet head and the gas in the confined space. Two kinds of large-scale vortex structure expedite the secondary coalescence and the final goblet-shaped liquid jet form. Cavities are observed on the dense liquid jet column as a result of the coalescence on the upstream. Consequently, the droplet breakup occurs more frequently on the downstream liquid jet under the gas phase disturbance. The viscous shear is created by the aerodynamic interaction, and the regular fish-scale structure is presented under the Kelvin-Helmholtz instability, which promotes the bulge surface to break into droplets. The research reveals the dynamic mechanism of the annular energetic liquid jet structural destabilization observed in the previous experiments. The combination of the structural instability and the surface instability facilitate the primary breakup of the annular energetic liquid jet, which is beneficial to improve the atomization and the combustion performance.